IMPLEMENTASI PERLINDUNGAN HAK-HAK MASYARAKAT MISKIN SEBAGAI HAK KONSTITUSIONAL DALAM MEMDAPATKAN PELAYANAN KESEHATAN DI KABUPATEN ROKAN HILIR - akbar, Rahmad; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Constitutional development has shifted from centralized to decentralized marked with the enactment of the Local Government Act, resulting in the shift of some tasks of the central government becomes the burden of responsibility in the area of managing. The Act contains a provision stating that the health sector is fully submitted to the Local Government with authority to manage and administer all aspects of health. Accordingly, Act No. 32 of 1992 on Health necessary adjustments with the spirit of regional autonomy. In this case I will focus on research in the area Rokan Hilir Government in the implementation of health services to the poor are classified continue to face problems in implementation.This type of research can be classified in socio-juridical research, because in this study the authors directly conduct research on the location or place under study in order to give a complete and clear picture of the problem under study. This research was conducted in jurisdictions Government Rokan Hilir, while the population and the sample is a whole party relating to the issues examined in this study, the data sources used, the primary data, secondary data, and the data tertiary data collection techniques in this study with observation, interview and literature study.From the research, there are three main issues that can be inferred: first, the implementation of health services for the poor in Rokan Hilir the form of Community Health Insurance (Jamkesmas) and the Regional Health Insurance (Jamkesda); second, inhibiting factor in the implementation of health services include internal factors such as lack of medical personnel, limited medical facilities, and Abuse of authority medical personnel, and external factors such as infrastructure constraints of non-medical and Geographic Conditions; Third, efforts made by the Government yanng Rokan Hilir in meeting the implementation of health care for the poor in Rokan Hilir include monitoring, coaching and training actions. Suggestions author, first, should have been the implementation of the provision of health care and social programs, also supported by the human resources as a medical team in providing good service and is responsible not only to patients, but also to God, because it is a social work community , Second, Rokan Hilir government should also consider the factors supporting each program, particularly in health services in poor communities, to meminimallisir constraints in the implementation of the provision of health services, third, efforts taken by the government should continue to pay attention to the various needs based kendala- constraints faced by the government in implementing health care programs, not just focus on the things that are technical health services it is of also matters is the formation of character and social.Keywords: Health - poor - Responsibility of Local Government